Bee health and veterinarians - Ritter, Wolfgang (World Organisation of Animal Health (OIE) ParisFR, 2014)
Aims to provide the veterinarian with a good basic knowledge of honey bees and apiculture. Describes the individual tasks of the veterinarian in the area of bee health, from practical handling of bees and sample extraction to diagnosis and control of bees diseases, implementation of official programmes on pest outbreak and poisoning control. Deals with the standards set by the OIE.